2021
DOI: 10.1016/j.intimp.2021.107825
|View full text |Cite
|
Sign up to set email alerts
|

Variant-genetic and transcript-expression analysis showed a role for the chemokine-receptor CCR5 in COVID-19 severity

Abstract: The chemokine receptor CCR5 has been implicated in COVID-19. CCR5 and its ligands are overexpressed in patients. The pharmacological targeting of CCR5 would improve the COVID-19 severity. We sought to investigate the role of the CCR5-Δ32 variant (rs333) in COVID-19. The CCR5 -Δ32 was genotyped in 801 patients (353 in the intensive care unit, ICU) and 660 healthy controls, and the deletion was significantly less frequent in hospitalysed COVID-19 than in healthy controls (p=0.01, OR=0.66 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…It is of interest that anti-CCR5 antibody leronlimab has been tried as a post-COVID-19 therapeutic molecule and shown to downregulate both inflammatory cytokine profile and the copy number of SARS-CoV2 RNA (22). In a recent study, the CCR5-32 variant was found to be significantly less frequent in hospitalized COVID-19 than in healthy controls (P = 0.01, OR = 0.66, 95% CI = 0.49-0.88), with no homozygotes found among the patients, compared to 1% of the controls (23). In addition, CCR5 transcript was expressed among the patients at significantly higher levels than in the healthy non-deletion carriers (P = 0.01).…”
Section: Discussionmentioning
confidence: 98%
“…It is of interest that anti-CCR5 antibody leronlimab has been tried as a post-COVID-19 therapeutic molecule and shown to downregulate both inflammatory cytokine profile and the copy number of SARS-CoV2 RNA (22). In a recent study, the CCR5-32 variant was found to be significantly less frequent in hospitalized COVID-19 than in healthy controls (P = 0.01, OR = 0.66, 95% CI = 0.49-0.88), with no homozygotes found among the patients, compared to 1% of the controls (23). In addition, CCR5 transcript was expressed among the patients at significantly higher levels than in the healthy non-deletion carriers (P = 0.01).…”
Section: Discussionmentioning
confidence: 98%
“…Last but not least, nowadays, the role of co-receptor 5 (CCR5) deletion 32 in coronavirus susceptibility is still controversial [77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…Functional blockade of CCR5 by maraviroc and CCR2 by clinical candidate agents to date has met with a fairly benign safety profile in patients across a range of indications. The homozygous Δ32 mutation of CCR5 has been reported as less prevalent in COVID-19 patients, with transcript levels higher in patients versus controls [103,104], although disease course has been reported with no association [105]. However, of particular note is the strong association of the Δ32 CCR5 genotype with increased susceptibility to West Nile virus infection [106,107].…”
Section: Safety Of Cvcmentioning
confidence: 99%